An overview of the quantification of fretting fatigue lives of complete contacts - Hills, D; Paynter, R; Dini, D (2012)
A procedure for quantifying the fretting fatigue damage arising at the edges of complete contacts subject to oscillatory loading is described. This relies on the Williams wedge analysis and permits: (a) the response of any prototype of complex geometry to be predicted, including the amount of fretting damage likely to be experienced and (b) the fretting fatigue strength measured in a simple laboratory experiment to be used to predict, reliably, the behaviour of any engineering component. © 2011 Elsevier Ltd.